Recent advances in curcumin nanoformulation for cancer therapy. (August 2014) - Lee, Wing-Hin; Loo, Ching-Yee; Young, Paul M; Traini, Daniela; Mason, Rebecca S; Rohanizadeh, Ramin
<x xml:space="preserve">Abstract</x> Introduction: Natural compounds are emerging as effective agents for the treatment of malignant diseases. Curcumin (diferuloylmethane), the active constituent of turmeric extract, has gained significant interest as a plant-based compound with anti-cancer properties. Curcumin is physiologically very well tolerated, with negligible systemic toxicity observed even after high oral doses administration. Despite curcumin's superior properties as an anti-cancer agent its applications are limited due to its low solubility and physico-chemical stability, rapid systemic clearance and low cellular uptake. Areas covered: This review focuses on the development of curcumin nano-particle formulation to improve its therapeutic index through enhanced cellular uptake, localization to targeted areas and improved bioavailability. The feasibility of nano-formulation in delivering curcumin and the limitations and challenges in designing and administrating the nano-sized curcumin particles are also covered in this review. Expert opinion: Nanotechnology is a promising tool to enhance efficacy and delivery of drugs. In this context, formulation of curcumin as nano-sized particles could reduce the required therapeutic dosages and subsequently reduced its cell toxicity. These nanoparticles are capable to provide local delivery of curcumin targeted to specific areas and thereby preventing systemic clearance. In addition, using specific coating, better pharmacokinetic and internalization of nano-curcumin could be achieved. However, the potential toxicity of nano-carriers for curcumin delivery is an important issue, which should be taken into account in curcumin nano-formulation.